Implementasi Tanggung Jawab Sosial Perusahaan (TJSP) di Kabupaten Purbalingga: (Studi Kasus PT Centra Sarana Pancing & PT Sumber Graha Sejahtera) - Pambajeng Luluh Dyah Pangestu (Universitas 17 Agustus 1945 Semarang, 2025)
Corporate Social Responsibility (CSR) is currently considered an important activity to be carried out by every company. CSR emphasizes the importance of companies to be committed and establish harmonious relationships with the community, environment, and government. PT Sumber Graha Sejahtera and PT Centra Sarana Pancing are two companies that have routinely implemented CSR. This study aims to analyze the implementation of CSR in Purbalingga Regency, especially in PT Sumber Graha Sejahtera and PT Centra Sarana Pancing. This study uses a qualitative descriptive method with data collection techniques in the form of observation, indeepth interview, and documentation. Although CSR has been implemented routinely, the results of the study indicate that the implementation of CSR is still not optimal and in accordance with applicable provisions. This can be seen from the minimal information related to the implementation of socialization responsibilities, minimal policy communication, minimal company knowledge related to the provisions of CSR implementation, and the absence of a CSR team. So that the company's contribution through CSR has not been implemented optimally.